A Novel Architecture for Community-Sustained Cultural Mapping System - Chong Eng, Tan; Sei Ping, Lau; Siew Mooi, Wong (The Science and Information (SAI) Organization Limited, 2022)
This paper presents a novel system architecture for implementing a cultural mapping system for the community of Buayan, a remote rural village in Sabah, East Malaysia. By considering various shortcomings of the local environment and the need for a community-sustained system, the cultural mapping system was designed to leverage a new set of architecture to achieve minimal implementation cost and higher reliability to survive the rural environment. The new architecture evolves from previous Telecentres’ design and implementation experience that was targeted at larger scale ICT systems. This paper also highlights the critical influence of power provision on the digital system implementation in rural areas, which always incurs a significant amount of the overall implementation cost. An efficient ICT system architecture will significantly reduce the cost of its associated power provision. The implementation of the cultural mapping system using the new ICT architecture at Buayan is also being described.